2015
DOI: 10.3109/10408363.2015.1050714
|View full text |Cite
|
Sign up to set email alerts
|

Vascular adhesion protein-1: Role in human pathology and application as a biomarker

Abstract: Vascular adhesion protein-1 (VAP-1) is a member of the copper-containing amine oxidase/semicarbazide-sensitive amine oxidase (AOC/SSAO) enzyme family. SSAO enzymes catalyze oxidative deamination of primary amines, which results in the production of the corresponding aldehyde, hydrogen peroxide and ammonium. VAP-1 is continuously expressed as a transmembrane glycoprotein in the vascular wall during development and facilitates the accumulation of inflammatory cells into the inflamed environment in concert with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(72 citation statements)
references
References 148 publications
1
68
0
Order By: Relevance
“…Thus, as expected, sVAP-1 and plasma SSAO activity showed tight correlation in our study. The membrane form of SSAO/VAP-1, highly expressed in endothelial cells, regulates leukocyte trafficking into site of inflammation (38). In obesity the membrane-bound VAP-1 is abundantly expressed on white fat cells, and is supposed to contribute to adipogenesis and pathological energy metabolism (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as expected, sVAP-1 and plasma SSAO activity showed tight correlation in our study. The membrane form of SSAO/VAP-1, highly expressed in endothelial cells, regulates leukocyte trafficking into site of inflammation (38). In obesity the membrane-bound VAP-1 is abundantly expressed on white fat cells, and is supposed to contribute to adipogenesis and pathological energy metabolism (38).…”
Section: Discussionmentioning
confidence: 99%
“…The membrane form of SSAO/VAP-1, highly expressed in endothelial cells, regulates leukocyte trafficking into site of inflammation (38). In obesity the membrane-bound VAP-1 is abundantly expressed on white fat cells, and is supposed to contribute to adipogenesis and pathological energy metabolism (38). It has been suggested that in obesity VAP-1 remains in the membrane-bound form, with a concurrent decrease in the circulating sVAP-1 concentration (39).…”
Section: Discussionmentioning
confidence: 99%
“…In the vascular endothelium, the extracellular domain may be cleaved off to give rise to a circulating form found in plasma. In some tissues, the membrane form acts as a Vascular Adhesion Protein (VAP‐1) which is involved in the migration of leukocytes through the vascular endothelium at sites of inflammation (Pannecoeck et al, ). This extravasion process requires the amine oxidase activity catalyzed by PrAO to be intact (Noonan, Lukas, Peet, & Pelletier, ).…”
Section: Introductionmentioning
confidence: 99%
“…Raised levels of PrAO are seen in a number of disease states including diabetes, Alzheimer's disease, and inflammation (Pannecoeck et al, ). The multiplicity of roles for PrAO in diverse processes has made it an important therapeutic target (O'Sullivan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the roles of ICAM-1 and VCAM-1 during leukocyte transmigration in most vascular beds have been extensively studied (8)(9)(10), additional adhesion molecules have also been shown to partake in the transmigration process of encephalitogenic immune cells, including activated leukocyte cell adhesion molecule (ALCAM/CD166) (11,12), melanoma cell adhesion molecule (MCAM) (13)(14)(15), mucosal vascular addressin cell adhesion molecule 1 (MAdCAM-1) (16,17), vascular adhesion protein (VAP-1) (18,19), Ninjurin-1 (20), and JAM-L (21). We have previously demonstrated that ALCAM is part of a group of adhesion molecules, found on BBB endothelial cells (BBB-ECs), that are involved in immune cell diapedesis (11,12).…”
mentioning
confidence: 99%